Calcium containing iron oxide as an efficient and robust catalyst in (photo-)electrocatalytic water oxidation at neutral pH. Issue 1 (16th November 2017) - Chiu, Hung-Chun; Huang, Wei-Hsiang; Hsu, Liang-Ching; Lin, Yan-Gu; Lai, Yi-Hsuan; Lin, Chia-Yu
Abstract : The amorphous nature and in situ formation of iron phosphate render CaFeO x with high activity and stability for the OER at neutral pH. Abstract : We report on calcium containing iron oxide thin films (CaFeO x ), prepared by spin-coating and a follow-up annealing process under mild condition, as an efficient and robust catalyst in electrocatalytic and photoelectrocatalytic water oxidation at neutral pH. Thin films prepared without calcium are essentially crystalline γ-Fe2 O3, but those prepared with calcium are amorphous, and with optimal calcium content, the resultant film consists of a short-range order γ-Fe2 O3 domain embedded in an amorphous Ca2 Fe2 O5 matrix. CaFeO x prepared with optimal calcium content decomposes upon exposure to phosphate, resulting in the leaching of surface calcium and formation of redox-active iron phosphate, which prevents the loss of active iron species from etching by protons released from the water oxidation process. The amorphous nature and in situ formation of iron phosphate render CaFeO x with high activity and stability under high turnover conditions, reaching 10 mA cm −2 at an overpotential ( η ) of ∼650 mV with a small increase in η (∼30 mV) over 2 h electrolysis in phosphate buffer (1.0 M, pH 7). When being integrated onto a BiVO4 photoanode, CaFeO x greatly improves the kinetics of the OER and interfacial hole transfer at BiVO4, resulting in remarkable enhancement in its photocurrent response and photostability.